A functional haplotype of UBE2L3 confers risk for systemic lupus erythematosus (2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease with diverse clinical manifestations characterized by the development of pathogenic autoantibodies manifesting in inflammation of target organs such as the kidneys, skin and joints. Genome-wide association studies have identified genetic variants in the UBE2L3 region that are associated with SLE in subjects of European and Asian ancestry. UBE2L3 encodes an ubiquitin-conjugating enzyme, UBCH7, involved in cell proliferation and immune function. In this study, we sought to further characterize the genetic association in the region of UBE2L3 and use molecular methods to determine the functional effect of the risk haplotype. We identified significant associations between variants in the region of UBE2L3 and SLE in individuals of European and Asian ancestry that exceeded a Bonferroni-corrected threshold (P and lt;1 × 10-4). A single risk haplotype was observed in all associated populations. Individuals harboring the risk haplotype display a significant increase in both UBE2L3 mRNA expression (P=0.0004) and UBCH7 protein expression (P=0.0068). The results suggest that variants carried on the SLE-associated UBE2L3 risk haplotype influence autoimmunity by modulating UBCH7 expression. © 2012 Macmillan Publishers Limited All rights reserved.